Crack propagation and strain-induced α’-martensite transformation in selective laser melting 316L stainless steels - Tan, Zhiheng; Gui, Maolei; Zhou, Zhiping; Lv, Jinlong; Zhang, Shuye; Wang, Zhuqing (Frontiers in Materials, 2023)
At present, in-situ monitoring of metal cracking and propagation is still a challenge. In this work, we used in-situ tensile tests with precast cracks of selective laser melting (SLM) and conventionally manufactured(CM) 316L stainless steels (SSs) to study crack propagation and strain-induced α′-martensite transformation. During in-situ tensile, cracks initiate at the concentration of slip lines at the precast crack, and the strong stress at the crack tip will tear apart the grain boundaries causing the crack to propagate until the samples are completely fractured. After in-situ tensile, abnormal grain growth was observed in the plastic zone at the crack tip of the SLMed 316L SS sample, while austenite to α′-martensite transformation was appeared at the grain boundaries of the SLMed 316L SS sample, and martensitic patches generated by severe plastic deformation induced in the CM 316L SS were also observed. The SLMed 316L SS was compared to have higher strength and resistance to deformation.